A refined model for the mechanical properties of polymer composites with nanorods having different length distributions. Issue 36 (25th May 2017) - Sapkota, Janak; Gooneie, Ali; Shirole, Anuja; Martinez Garcia, Julio Cesar
ABSTRACT: The aspect ratio of rod‐like nanofillers is an important factor that governs their percolation threshold in nanocomposites with a polymer of interest. Controlling the length distribution of a filler is an effective way to manipulate the onset of network formation and thereby materials properties that are related to the latter. The use of two or more different filler types with dissimilar aspect ratio is a special case to achieve such control. We here report the modification of an existing mechanical model to describe the mechanical properties of polymer nanocomposites with a binary length distribution of nanofillers. The model was exemplarily applied to materials comprised of two nanorod types having high and low aspect ratio, respectively, and used to explain why the properties of such nanocomposites are strongly weighted by the nanorod type characterized by a higher aspect ratio and stiffness. © 2017 Wiley Periodicals, Inc. J. Appl. Polym. Sci.2017, 134, 45279. Abstract :